Catalytic oxidation of cyclohexane by substituted metalloporphyrins: experimental and molecular simulation. Issue 123 (25th November 2015) - Feng, Ze; Xie, Yujia; Hao, Fang; Liu, Pingle; Luo, He'an
Abstract : The metalloporphyrins and metalloporphyrin intermediates with lower energy gap have stronger ability to activate the oxygen and cyclohexane respectively. Abstract : A series of meso -substituted metal tetraphenylporphyrins were synthesized and characterized by UV-vis, FT-IR and elemental analysis. The experimental results show that cobalt tetra(4-nitrophonyl)porphyrin (Co–TNPP) gives better catalytic performance in cyclohexane oxidation. The KA oil (cyclohexanol and cyclohexanone) selectivity is 79.54% at the cyclohexane conversion of 10.43%, and the turnover number reaches to 0.93 × 10 4 . Cyclohexane oxidation catalyzed by meso -substituted metalloporphyrins was studied by molecular simulation and experiment. The results of molecular simulation performed by Materials Studio show that the substituted electron-withdrawing groups in the same central metal porphyrins reduce the HOMO and LUMO energies. The metalloporphyrins with lower energy gap have stronger ability to activate the oxygen, the metalloporphyrin intermediates with lower energy gap have stronger ability to activate the cyclohexane.